Image Processing for Combat Charcoal Identification Based on Maturity Level - Musthafa Haris Munandar; Masrizal Masrizal; Yudi Prayoga (Jurnal Mantik, 2021)
At this time the processing of coconut shells into shell charcoal is very much done by ordinary people, especially in villages that have a large coconut population. This is because the benefits obtained from the processing of coconut shells can meet the needs of the community. The many desires of the people who want to do the processing of coconut shells, but not accompanied by sufficient knowledge and knowledge of the quality of charcoal desired by buyers, so it is undeniable that the number of coconut shells that have been processed into charcoal but not sold in the market. o with this, it is expected that after using the image processing method can provide knowledge and knowledge to the public about the quality of charcoal that buyers expect, especially to identify the difference in coconut shells that are still not charcoal, coconut shells that are half into charcoal and coconut shells that have become charcoal. This image processing method will classify coconut shell charcoal based on digital imagery with a media interface GUI (Graphical User Interface) that utilizes matlab software.